JUNIOR-SENIOR HIGH SCHOOL BASED ON PESANTREN BOARDING SYSTEM - Abdul Rohman (Jurnal Pendidikan Islam, 2014)
The study is aimed to uncover that a boarding system in junior-senior high school (SMP-SMA) Semesta Billingual Boarding School (BBS) Semarang adopted the pesantren style. This is evidenced by the fact that, like pesantren, the typical of boarding school in BBS Semarang puts more emphasis on strengthening the affective (akhlāq) aspects, because of; 1) the curriculum of all subjects in school mutually integrated, 2) the curriculum design by the development of self-habituation, 3) design through creating climate and culture, 4) constitute the hidden curriculum, 5) more "mutually adaptive" and dominated by transmission model rather than transaction and transformation model, 6) can be used as an eclectic systems, between constructivist and non-constructivist, the social and personal model, the information and processing model, the humanism and behavioral oriented. The main purpose of the schools adopts the boarding school system to maintain and improve the quality of learners morals. However by adopting such system, learners can be monitored for almost 24 hours because they had been living in the college. Thus, adopting a boarding school system can be a solution to overcome and reduce morale among students dekandensi Indonesia and even in other countries.